2019
DOI: 10.3390/nu11081792
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Beetroot Juice on Blood Pressure, Microvascular Function and Large-Vessel Endothelial Function: A Randomized, Double-Blind, Placebo-Controlled Pilot Study in Healthy Older Adults

Abstract: : Dietary nitrate (NO3−) has been reported to improve endothelial function (EF) and blood pressure (BP). However, most studies only assess large-vessel EF with little research on the microvasculature. Thus, the aim of the present pilot study is to examine NO3− supplementation on microvascular and large-vessel EF and BP. Twenty older adults (63 ± 6 years) were randomized to a beetroot juice (BRJ) or placebo (PLA) group for 28 (±7) days and attended three laboratory visitations. Across visitations, blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 55 publications
7
31
0
2
Order By: Relevance
“…The lack of any BP effect likely reflects the accepted dogma that the magnitude of BP reduction expected from any single dose of antihypertensive agent is proportional to basal BP level (Law et al, 2003). However, this result is at odds with the majority of studies that demonstrate BP lowering in normotensive persons after systemic nitrite elevation after inorganic nitrate supplementation (Table 1) (Larsen et al, 2006;Webb et al, 2008b;Bailey et al, 2009Bailey et al, , 2010Kapil et al, 2010;Sobko et al, 2010;Vanhatalo et al, 2010;Lansley et al, 2011a,b;Bahra et al, 2012;Bondonno et al, 2012Bondonno et al, , 2014bCermak et al, 2012a;Coles and Clifton, 2012;Bond et al, 2013Bond et al, , 2014Joris and Mensink, 2013;Kelly et al, 2013;Liu et al, 2013;Wylie et al, 2013;Jajja et al, 2014;Rammos et al, 2014;Ashor et al, 2015;Ashworth et al, 2015;Bourdillon et al, 2015;Jovanovski et al, 2015;Lee et al, 2015;Choi et al, 2016;Flueck et al, 2016;Jonvik et al, 2016;Raubenheimer et al, 2017;Jones et al, 2019). The first contemporary demonstration of BP-lowering effect of inorganic nitrate via conversion to nitrite used NaNO 3 [0.1 mmol/kg (6.2 mg/kg)] daily for 3 days compared with matched NaCl control in 17 healthy subjects.…”
Section: A Nitrite Nitrate and The CV Systemmentioning
confidence: 99%
“…The lack of any BP effect likely reflects the accepted dogma that the magnitude of BP reduction expected from any single dose of antihypertensive agent is proportional to basal BP level (Law et al, 2003). However, this result is at odds with the majority of studies that demonstrate BP lowering in normotensive persons after systemic nitrite elevation after inorganic nitrate supplementation (Table 1) (Larsen et al, 2006;Webb et al, 2008b;Bailey et al, 2009Bailey et al, , 2010Kapil et al, 2010;Sobko et al, 2010;Vanhatalo et al, 2010;Lansley et al, 2011a,b;Bahra et al, 2012;Bondonno et al, 2012Bondonno et al, , 2014bCermak et al, 2012a;Coles and Clifton, 2012;Bond et al, 2013Bond et al, , 2014Joris and Mensink, 2013;Kelly et al, 2013;Liu et al, 2013;Wylie et al, 2013;Jajja et al, 2014;Rammos et al, 2014;Ashor et al, 2015;Ashworth et al, 2015;Bourdillon et al, 2015;Jovanovski et al, 2015;Lee et al, 2015;Choi et al, 2016;Flueck et al, 2016;Jonvik et al, 2016;Raubenheimer et al, 2017;Jones et al, 2019). The first contemporary demonstration of BP-lowering effect of inorganic nitrate via conversion to nitrite used NaNO 3 [0.1 mmol/kg (6.2 mg/kg)] daily for 3 days compared with matched NaCl control in 17 healthy subjects.…”
Section: A Nitrite Nitrate and The CV Systemmentioning
confidence: 99%
“…Beetroot is known for its antioxidant activities and widely used as a remedy for a variety of ailments including cardiovascular-related conditions, anemia, sexual weakness and bladder stones [2]. Some recent clinical studies have also indicated the usefulness of beetroot in managing blood pressure and cardiovascular health [3][4][5][6]. Beetroot has also gained popularity as a supplement to boost energy and improve performance in athletes [7][8][9][10].Interestingly, in the Traditional Persian Medicine practices, beetroot is one of the foods used in the prevention and managing of metastatic progression of cancer [11].…”
mentioning
confidence: 99%
“…From a mechanistic perspective, we reason that the additive effects of nitric oxide - derived through chronic beetroot juice ingestion and repetitive shear stress invoked during resistance exercise training sessions (3 times per week for 8 weeks) [ 70 ] - will result in more robust endothelium-dependent vascular adaptations when compared to exercise training alone. Separately, dietary nitrate and habitual exercise training interventions have favorably influenced blood pressure [ 19 , [71] , [72] , [73] ], macrovascular [ 7 , 73 , 74 ], and microvascular function [ 75 ] in healthy older men and women. However, the cumulative effect of dietary nitrate coupled with exercise training has not yet been compared to exercise training alone, and it is further unknown whether such interventions will elicit differing adaptations in conduit or resistance vessels [ 63 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Separately, dietary nitrate and habitual exercise training interventions have favorably influenced blood pressure [ 19 , [71] , [72] , [73] ], macrovascular [ 7 , 73 , 74 ], and microvascular function [ 75 ] in healthy older men and women. However, the cumulative effect of dietary nitrate coupled with exercise training has not yet been compared to exercise training alone, and it is further unknown whether such interventions will elicit differing adaptations in conduit or resistance vessels [ 63 , 73 ]. As such, we are assessing changes in both macrovascular (brachial artery diameter) and microvasculature (cutaneous vascular conductance) function using flow-mediated vasodilation and laser-Doppler flowmetry, respectively, following EX + BR compared with EX and EX + PL.…”
Section: Discussionmentioning
confidence: 99%